Relationship of Hemoglobin Concentration at Admission and Need for Erythroyte Transfusion During Hospitalization with Mortality in Pediatric Critical Care Patients - Ali Ertuğ Arslanköylü; Barış Akbaş; Mehmet Alakaya; Gülçin Bozlu; Asena Ayça Özdemir (Journal of Pediatric Emergency and Intensive Care Medicine, 2017)
Introductıon: This study aimed to investigate the relationship of hemoglobin concentration at admission to pediatric intensive care unit and erythrocyte transfusion during hospitalization with mortality. Methods: In this prospective study, we included 260 patients who were admitted to a 12-bed pediatric intensive care unit in a one-year period. Demographic characteristics, admission etiologies, length of stay in the pediatric intensive care unit, mechanical ventilation rates, pediatric risk of mortality III and pediatric logistic organ dysfunction scores, complete blood count on admission and erythrocyte transfusion during hospitalization were recorded prospectively. Results: Of the 260 cases, 34 were exitus. The mortality rate was 13%. The mean hemoglobin concentration of patients who were exitus was lower than that of patients who survived (10.55±2.45 g/dL vs. 10.55±2.45 g/dL, p=0.011). Although platelet levels were lower in patients who were exitus than in survivors, the difference was not statistically significant (320.352±181.731/mm3 vs. 352.231±174,129/mm3 p=0.325). The mortality rate in transfused patients was higher than in patients who were not transfused. (40.2% vs. 1.6%, p<0.001). Conclusion: Hemoglobin concentration at admission in patients who die in pediatric intensive care unit is significantly lower than in those who survive. In this study, increased mortality risk in patients admitted to pediatric intensive care unit was found to be associated with the presence of anemia and need for erythrocyte transfusion.